If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 25 = -5 + -1y Reorder the terms: 25 + 5y = -5 + -1y Solving 25 + 5y = -5 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 25 + 5y + y = -5 + -1y + y Combine like terms: 5y + y = 6y 25 + 6y = -5 + -1y + y Combine like terms: -1y + y = 0 25 + 6y = -5 + 0 25 + 6y = -5 Add '-25' to each side of the equation. 25 + -25 + 6y = -5 + -25 Combine like terms: 25 + -25 = 0 0 + 6y = -5 + -25 6y = -5 + -25 Combine like terms: -5 + -25 = -30 6y = -30 Divide each side by '6'. y = -5 Simplifying y = -5
| -2x+5=x-12 | | 15-2=15 | | (x^3+4x^2-5x)-(4x^3+x^2-7)= | | -x(-8)-4y=16 | | -4x+9=35 | | 13k+3(k+11)=8k+-7 | | 3y+2=12-y | | 6b-.2=7b | | 5d-27=108 | | 25(C-55)=23750 | | X(2x+1)+4(2x+1)=0 | | 2*(3t^2)*(4t^2-1)=x | | 19+x=14 | | 2k+-2.6=12 | | -6t-8=-7t | | f(x)=3x^3-x^2+5x | | -8g=-9g-2 | | 3p-3=2 | | N-6=2n-16 | | X-.3x=114 | | -9(0)-2y=-20 | | 1.75y^2+2y=0 | | 7n+2=8 | | 22222x+69x=4 | | (x+y-z)(x+y+z)= | | 5y+3=y+1 | | An=(2n^2) | | 5x^3-15x^2+4x-12=0 | | x+(x-2)+2x=82 | | 43+26k=927 | | X^2-12-27=0 | | 8a+5=10 |